Analisa Tensile Strength Komposit Serat Kulit Pohon Waru dengan Kombinasi Serat Karbon Kevlar Sebagai Material Reinforcement - Stefan Enus, Handry; Soebiyakto, Gatot; Rizki Fadhillah, Arief; Hermawan, Dadang (Infotekmesin, 2023)
In increasing the tensile strength of the waru tree bark fiber composite (Hibiscus tiliaceus), it is necessary to have a combination of reinforcement used in the composite material. One of the reinforcement materials that can be combined is carbon fiber kevlar. Kevlar carbon fiber has several advantages, including low density, absorbing vibrations well, and it is resistant to chemical solutions. The specific objectives of this study were to determine the maximum strain stress, modulus of elasticity, and fracture analysis of hibiscus bark fiber composites with a combination of kevlar carbon fiber as a reinforcement material. The independent variable in the study was comparing the composite with the different reinforcement materials used, including 100% hibiscus (Hibiscus tiliaceus) bark fiber, 100% kevlar carbon fiber, 50% combination fiber of hibiscus (Hibiscus tiliaceus) bark, and 50% kevlar carbon. The process of making composites uses the vacuum infusion resin method with specimens referring to the ASTM D638-03 type I standard. The results of this study are that combining kevlar carbon fiber as a reinforcement material can improve the mechanical properties in terms of the tensile strength of the hibiscus tree bark fiber composite.